Quantification of Free Circulating DNA As a Diagnostic Marker in Lung Cancer - Sozzi, Gabriella; Conte, Davide; Leon, MariaElena; Cirincione, Rosalia; Roz, Luca; Ratcliffe, Cathy; Roz, Elena; Cirenei, Nicola; Bellomi, Massimo; Pelosi, Giuseppe; Pierotti, Marco A.; Pastorino, Ugo (Journal of clinical oncology, 2003)
Purpose: Analysis of circulating DNA in plasma can provide a useful marker for earlier lung cancer detection. This study was designed to assess the sensitivity and specificity of a quantitative molecular assay of circulating DNA to identify patients with lung cancer and monitor their disease. Materials and Methods: The amount of plasma DNA was determined through the use of real-time quantitative polymerase chain reaction (PCR) amplification of the human telomerase reverse transcriptase gene (hTERT) in 100 non–small-cell lung cancer patients and 100 age-, sex-, and smoking-matched controls. Screening performance of the assay was calculated through the receiver operating characteristic (ROC) curve. Odds ratios were calculated using conditional logistic regression analysis. Results: Median concentration of circulating plasma DNA in patients was almost eight times the value detected incontrols (24.3 v 3.1 ng/mL). The area under the ROC curve was 0.94 (95% CI, 0.907 to 0.973). Plasma DNA was a strong risk factor for lung cancer; concentrations in the upper tertile were associated with an 85-fold higher risk than were those in the lowest tertile. Conclusion: This study shows that higher levels of free circulating DNA can be detected in patients with lung cancer compared with disease-free heavy smokers by a PCR assay, and suggests a new, noninvasive approach for early detection of lung cancer. Levels of plasma DNA could also identify higher-risk individuals for lung cancer screening and chemoprevention trials.